VD_FINDINFO HC / 2021 / 510 vom 10. September 2021 - VD Tribunal cantonal (2021)
CAUSE DE DIVORCE, OBLIGATION D'ENTRETIEN, RELATIONS PERSONNELLES | 125 CC, 273 al. 1 CC, 285 CC, 308 al. 1 let. a CPC (CH)